Aerodynamics in train cross wind studies. (1st January 2014) - Allain, E.; Paradot, N.
This paper presents the global status of aerodynamic studies for railways crosswind. European regulations and aerodynamic process are presented as well as some current issues with a focus on the ground configuration choice. An example of study achieved on TGV Duplex power car is given. The aim of this study was to compare the results obtained through numerical simulations and wind tunnel tests for a specific ground configuration.